Chapter 35 Migration and Narrative Dynamics - Sommer, Roy (Taylor & Francis, 2023)
How can narrative theory account for the changing roles of storytelling and storysharing in the public sphere? This essay proposes a new concept of narrative dynamics, one that generates well-constrained descriptions of specific elements, features, or qualities of narratives, as well as programmatic claims concerning their potential uses and effects. Narrative dynamics research is equally interested in the pragmatics of strategic framing and the grand narratives of human rights, in mundane stories of everyday experience and the intangible myths and masterplots which shape organizations, institutions, and cultures. Starting with the formal characteristics and functional qualities of narrative that contribute to its interactivity, the essay discusses phenomena such as narrative aggregation and normalization, event modeling, and narrative chaff. It then demonstrates how these new concepts produce new insights in the narrative ecology of the public sphere, by analysing key moments in European migration discourses since 2015.